Comparison of different regimens of estradiol benzoate treatments followed by long-acting progesterone to prepare noncycling mares as embryo recipients - Silva, E. S. M. [UNESP]; Roser, J. F.; Gomes, A. R. C. [UNESP]; Fritsch, S. C. [UNESP]; Pantoja, J. C. F. [UNESP]; Oliveira-Filho, J. P. [UNESP]; Meira, C. [UNESP] (Elsevier B.V., 2016)
The present study evaluated the influence of different regimens of estradiol benzoate (EB) treatments followed by a single dose of long-acting progesterone (LA P4) on plasma estrogen and P4 concentrations in noncyclic mares prepared as embryo recipients. Twenty-one anestrous mares were distributed into three groups (n = 7 mares per group), according to the EB dose received (single dose of 2.5 mg, total of 5 mg in decreasing doses, and total of 10 mg in decreasing doses), which was followed by a single administration of 1500 mg of LA P4 in all groups. Mares were reevaluated during the ovulatory phase and seven of them became part of the cyclic nontreated control group. Ultrasonography was performed to monitor endometrial edema, and blood samples were collected to measure estradiol (E2), estrogen conjugate (EC), and P4 by RIA. Maximum uterine edema was achieved 24 hours after administration of EB in all treated groups. Maximum E2 concentrations were observed 24 hours after the first EB injection in treated groups and there were no differences (P > 0.05) among treatments. Maximum EC concentration was observed 24 hours after the single EB injection in the 2.5-mg group, whereas in the 5- and 10-mg groups EC peaks were observed 48 hours after the first EB administration. Maximum P4 concentrations were detected 24 hours after LA P4 injection, although higher P4 concentrations were observed in the group treated with 2.5 mg of EB than in that treated with 10 mg of EB (P < 0.05). Because P4 concentrations were reduced after administration of high doses of EB, we also measured 17 alpha-hydroxyprogesterone (17-OH-P) to test the hypothesis that high concentrations of EB would accelerate the conversion of P4 to 17-OH-P. However, 17-OH-P concentrations paralleled P4 profile in all groups, irrespective of EB doses. In summary, the three EB treatment regimens induced similar E2 peaks, although the observation of EC peaks 24 hours after E2 peaks in the 5- and 10-mg groups indicate that an excess of E2 was given, which was converted into EC to be inactivated. Administration of 10 mg of EB reduced P4 concentrations 24 hours after LA P4 was given. We demonstrated that the mechanism by which this reduction occurred was not by an increase in P4 metabolism to 17 alpha-OH-P. In conclusion, the use of 2.5 mg of EB followed by 1500 mg of LA P4 appears to be a more appropriate regimen to treat noncyclic mares, although additional studies are needed to verify embryo survival with this treatment dose. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Equine embryo transfer; Recipient mares; Hormonal protocols; Estrogen; Progesterone